PERAN PELATIHAN DAN PENGEMBANGAN DALAM MENINGKATKAN KOMPETENSI SDM DI PT SEMEN INDONESIA LOGISTIK - Fitri, Masfiyah Zulia; Atho’illah, Akhmad Yunan (Relawan Jurnal Indonesia, 2025)
This research aims to analyze the role of training and development in improving human resource (HR) competencies at PT Semen Indonesia Logistik (SILOG). The method used is descriptive qualitative with data collection techniques through document analysis and interviews. The results of the study indicate that the implementation of training at PT SILOG is structured based on a learning needs diagnosis using the STAR method (Situation, Task, Action, Result), making the training programs more targeted. The framework used includes three main stages: design, delivery, and evaluation. The evaluation stage is conducted six months to one year after training to assess the program's effectiveness. Training and development have proven to play a crucial role in enhancing HR competencies, which include knowledge, skills, and attitudes.